Nonlinear Performance Characteristics of Flux-Switching PM Motors - E. Ilhan; M. F. J. Kremers; T. E. Motoasca; J. J. H. Paulides; E. A. Lomonova (Journal of Engineering)
Nonlinear performance characteristics of 3-phase flux-switching permanent magnet motors (FSPM) are overviewed. These machines show advantages of a robust rotor structure and a high energy density. Research on the FSPM is predominated by topics such as modeling and machine comparison, with little emphasis given on its performance and limits. Performance characteristics include phase flux linkage, phase torque, and phase inductance. In the paper, this analysis is done by a cross-correlation of rotor position and armature current. Due to the high amount of processed data, which cannot be handled analytically within an acceptable time period, a multistatic 2D finite element model (FEM) is used. For generalization, the most commonly discussed FSPM topology, 12/10 FSPM, is chosen. Limitations on the motor performance due to the saturation are discussed on each characteristic. Additionally, a focused overview is given on energy conversion loops and dq-axes identification for the FSPM.